Near‐field observations of an offshore Mw 6.0 earthquake from an integrated seafloor and subseafloor monitoring network at the Nankai Trough, southwest Japan. Issue 11 (18th November 2016) - Wallace, L. M.; Araki, E.; Saffer, D.; Wang, X.; Roesner, A.; Kopf, A.; Nakanishi, A.; Power, W.; Kobayashi, R.; Kinoshita, C.; Toczko, S.; Kimura, T.; et al.
Abstract: An Mw 6.0 earthquake struck 50 km offshore the Kii Peninsula of southwest Honshu, Japan on 1 April 2016. This earthquake occurred directly beneath a cabled offshore monitoring network at the Nankai Trough subduction zone and within 25–35 km of two borehole observatories installed as part of the International Ocean Discovery Program's NanTroSEIZE project. The earthquake's location close to the seafloor and subseafloor network offers a unique opportunity to evaluate dense seafloor geodetic and seismological data in the near field of a moderate‐sized offshore earthquake. We use the offshore seismic network to locate the main shock and aftershocks, seafloor pressure sensors, and borehole observatory data to determine the detailed distribution of seafloor and subseafloor deformation, and seafloor pressure observations to model the resulting tsunami. Contractional strain estimated from formation pore pressure records in the borehole observatories (equivalent to 0.37 to 0.15 μstrain) provides a key to narrowing the possible range of fault plane solutions. Together, these data show that the rupture occurred on a landward dipping thrust fault at 9–10 km below the seafloor, most likely on the plate interface. Pore pressure changes recorded in one of the observatories also provide evidence for significant afterslip for at least a few days following the main shock. The earthquake and its aftershocks are located within the coseismic slip region of the 1944 Tonankai earthquake ( Mw 8.0), and immediately downdip of swarms of very low frequency earthquakes in this region, illustrating the complex distribution of megathrust slip behavior at a dominantly locked seismogenic zone. Key Points: Unique near‐field seafloor observations of an Mw 6.0 offshore subduction earthquake An Mw 6.0 earthquake on 1 April 2016 ruptured the plate interface in the source area of great earthquakes at the Nankai Trough Interseismic behavior within the seismogenic zone of a subduction plate boundary fault can be spatially and temporally complex